Nabro volcano aerosol in the stratosphere over Georgia, South Caucasus from ground-based spectrometry of twilight sky brightness - N. Mateshvili; D. Fussen; G. Mateshvili; I. Mateshvili; F. Vanhellemont; E. Kyrölä; S. Tukiainen; J. Kujanpää; C. Bingen; C. Robert; C. Tétard; E. Dekemper (Atmospheric Measurement Techniques, 2013)
Ground-based spectral measurements of twilight sky brightness were carried out between September 2009 and August 2011 in Georgia, South Caucasus. The algorithm which allowed to retrieve the lower stratospheric and upper tropospheric aerosol extinction profiles was developed. The Monte-Carlo technique was used to correctly represent multiple scattering in a spherical atmosphere. The estimated stratospheric aerosol optical depths at a wavelength of 780 nm were: 6 × 10−3 ± 2 × 10−3 (31 August 2009–29 November 2009), 2.5 × 10−3 ± 7 × 10−4 (20 March 2010–15 January 2011) and 8 × 10−3 ± 3 × 10−3 (18 July 2011–3 August 2011). The optical depth values correspond to the moderately elevated stratospheric aerosol level after the Sarychev eruption in 2009, background stratospheric aerosol layer, and the volcanically disturbed stratospheric aerosol layer after the Nabro eruption in June 2011. <br. Reconsideration of measurements acquired soon after the Pinatubo eruption in 1991 allowed to model the phenomenon of the "second purple light", a twilight sky brightness enhancement at large solar zenith angles (97–102°). Monte-Carlo modelling reveals that the second purple light is caused by multiple scattering in the stratospheric aerosol layer.